First Crack Guided Conservative Posterior Capsulotomy Using Neodymium: YAG Laser - Naeem Akhtar Katpar, Syed Imtiaz Ali Shah, Shujaat Ali Shah, Partab Rai, Safdar Ali Abbasi (Pakistan Journal of Ophthalmology, 2016)
Purpose: To report a new method of Nd: YAG laser posterior capsulotomy (first crack guided conservative posterior capsulotomy). Study Design: Prospective case series study. Place and duration of study: This study was conducted from January 2001 to January 2015 at the Department of Ophthalmology, Chandka Medical College Hospital, Larkana, Pakistan. Material and Methods: In this study, 670 eyes of 623 patients with clinically diagnosed posterior capsular opacification following extra capsular cataract extraction or phacoemulsification and posterior chamber IOL implantation, were included. Patients with Aphakia, Anterior chamber IOL, High myopia, Uveitis, Uncontrolled glaucoma, Maculopathies, Optic nerve diseases and patients below 20 years of age were excluded from the study. Pre-procedure best corrected visual acuity (BCVA) and IOP was noted and complete clinical examination was done. Nd: YAG laser posterior capsulotomy was performed. The patients were seen one hour after capsulotomy, then after 24 hours and then weekly for 3 weeks. Post-procedure best corrected visual acuity (BCVA) and any complications seen were recorded. SPSS version 20 was used for data entry and analysis. Results: Out of the total 623 patients 398 (63.88%) were males and 225 (36.12%) were females. Mean age ± standard deviation was 55.39 ± 13.16 years and age range was 20 to 78 years. Most of the patients belonged to the 51 – 60 years age group. Interval between cataract surgery and Nd: YAG laser posterior capsulotomy ranged from 6 months to